The Moderating Role of Academic Self-Efficacy in the Relationship between Social Comparison and Hypercompetitiveness : The Different Effects Among Urban and Rural Group Students in Indonesia - Dumbi, Khairunnisa Syafira; Djuwita, Ratna (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to exploreÂ the relationship between social comparison and hypercompetitiveness, and the moderating effects of academic self-efficacy. In addition, we also compare the different effects among urban group students and rural group students. This study used a non-experimental design witha quantitative approach. The final participants included 146 high school students aged between 15-18 years. There are three instruments used in this study: the Hypercompetitiveness in Academic Scale (HIA) for measuring hypercompatitiveness, the Iowa-Netherlands Comparison Orientation Measure (INCOM) for measuring social comparison, and the Academic Self-Efficacy Scale (TASES) for measuring self-efficacy specific in academic setting. All of the data questionnaires were analyzed by descriptive, correlation, and moderation analysis. The result shows that academic self-efficacy plays a significant role in the association between social comparison and hypercompetitiveness. In addition, the relationship between these three variables is differentÂ for urban and rural students. Taken together, these findings can provide theoretical and practical guidance for teachers, counselors, and school psychologists to understand hypercompetitiveness characteristics among students, increase their awareness about hypercompetitiveness characteristics,Â and provide supportÂ through counseling or training that can encourage collaborative work among students and improve their academic self-efficacy.